Thermal Sensation Assessment by Young Portuguese Adults in Controlled Settings - Coelho, Denis (2019)
Laboratory experiments in a controlled climatic chamber enabled evaluation of fitness of the PMV equation to thermal sensation assessment by a Portuguese sample. Experiments were carried out in two occasions (May and December 2014), with two different college students cohorts, with 5 experimental condi-tions in each cohort. A total of 323 individual assessments of specific controlled thermal environment condi-tions were collected. Subjects sat down in a chair while inside the chamber and evaluated the thermal envi-ronment after a standard period of 3 minutes inside the controlled climate chamber. Each participating subject undertook the sitting in the chamber in five different days, with different climatic conditions each time. PMV and thermal sensation as assessed in the climatic chamber are compared, yielding correlation coefficients which differ between the Spring-Summer experiments and the Autumn-Winter Experiments but not between genders. The paper discusses possible factors contributing to different correlations obtained in the Autumn-Winter and the Spring-Summer experiments.